2005
DOI: 10.1210/jc.2004-2359
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibition of the Hypothalamic Gonadotropin-Releasing Hormone Pulse Generator: Evidence for Varied Effects in Hyperandrogenemic Adolescent Girls

Abstract: Compared with normal women, adults with polycystic ovarian syndrome (PCOS) require higher progesterone (P) concentrations to inhibit GnRH (LH) pulse frequency, which contributes to persistently rapid GnRH pulses and elevated LH levels in PCOS. To explore the origin of this abnormality, we assessed hypothalamic sensitivity to P feedback in nine normal controls and 11 hyperandrogenemic (HA) adolescents. Subjects first underwent frequent blood sampling for 11 h to assess baseline LH pulse frequency. Thereafter, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 19 publications
1
48
1
4
Order By: Relevance
“…Decreased sensitivity to P 4 feedback is seen in about one-half of PCOS patients and HA adolescents (22,68), and has also been reported in adult female sheep that were treated prenatally with T (72). Visual inspection of the current data (see Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Decreased sensitivity to P 4 feedback is seen in about one-half of PCOS patients and HA adolescents (22,68), and has also been reported in adult female sheep that were treated prenatally with T (72). Visual inspection of the current data (see Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Like adults with PCOS, obese girls with HA have increased levels of LH and decreased sensitivity to P 4 negative feedback (22,49). In late puberty, girls with obesity reportedly have increased frequency of pulsatile LH release compared with nonobese girls (57).…”
mentioning
confidence: 99%
“…Centrally, androgen excess may reduce hypothalamic feedback inhibition, resulting in increased GnRH pulsatility, particularly during puberty [40]. GnRH stimulation results in an increase in LH/FSH ratio in women with PCOS and recent studies have revealed that women with PCOS have higher baseline and GnRH-stimulated LH concentrations [41].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that PCOS and NC CAH women had increased LH pulse amplitude compared with control women, but only PCOS women had decreased LH interpulse interval compared with controls. Data suggesting abnormalities of LH pulsatility in PCOS women are related to a relative insensitivity to progesterone-induced LH inhibition (6,7,8,9), an abnormality that can be reversed by blockade of androgen action (10). Gonadotropin abnormalities of NC CAH women therefore appear to be intermediate between those of controls and PCOS patients (5).…”
Section: Introductionmentioning
confidence: 99%